PENGARUH CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU DALAM PELAPORAN KEUANGAN - Nurfitri Ayu Widiyaswari (2020)
This research was conducted to examine the effect of corporate governance on timeliness in financial reporting, with research variabels including reporting lag, audit committee meeting, audit committee size, audit committee financial expertise, and audit committee independence. The sampling method uses purposive sampling. The research sample consisted of 648 companies listed on the Indonesia Stock Exchange (IDX) for the period of 2017- 2018. The study uses STATA 13 to test hypotheses with Multiple Linear Regression Analysis with a significance level of 5% (0.05). The results of testing can be obtained that (1) audit committee independence does not has a significantly influence reporting lag; (2) audit committee financial expertise does not has a significantly influence reporting lag, (3) audit committee size does not has a significantly influence reporting lag, (4) audit committee meeting does has a significantly influence reporting lag.